2021
DOI: 10.3389/fmicb.2021.708712
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Antibacterial Role of Peptide From Bacillus subtilis subsp. spizizenii Ba49 Against Staphylococcus aureus

Abstract: An increase in antibiotic resistance has led to escalating the need for the development of alternate therapy. Antimicrobial peptides (AMPs) are at the forefront of replacing conventional antibiotics, showing slower development of drug resistance, antibiofilm activity, and the ability to modulate the host immune response. The ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) pathogens that jeopardize most conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…In this study, Spgillcin 177–189 showed potent antimicrobial effects against S. aureus without resistance, and Spgillcin 177–189 could effectively kill S. aureus in the culture supernatant of RAW 264.7 cells. This result was similar to the AMP Ba49, which exhibits a potential bactericidal activity against S. aureus in macrophage cells ( Taggar et al., 2021 ), and the AMP CATH-2, which kills S. aureus in macrophage cells ( Schneider et al., 2017 ). Therefore, Spgillcin 177–189 could be exploited as an effective anti-infective drug in the future.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, Spgillcin 177–189 showed potent antimicrobial effects against S. aureus without resistance, and Spgillcin 177–189 could effectively kill S. aureus in the culture supernatant of RAW 264.7 cells. This result was similar to the AMP Ba49, which exhibits a potential bactericidal activity against S. aureus in macrophage cells ( Taggar et al., 2021 ), and the AMP CATH-2, which kills S. aureus in macrophage cells ( Schneider et al., 2017 ). Therefore, Spgillcin 177–189 could be exploited as an effective anti-infective drug in the future.…”
Section: Discussionsupporting
confidence: 70%
“…It is involved in maintaining the dynamic balance of bacterial proton dynamics and is essential for bacterial survival. We next evaluated the effect of GK-4 peptide on membrane potential using the fluorescent dye DiSC 3 (5) [ 35 ], as it accumulates in the cytoplasmic membrane in response to the Δψ component of bacteria. When Δψ is destroyed, the probe will be released into the extracellular environment, resulting in fluorescence enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…In Taggar et al’s study, an AMP, named peptide-Ba49, was isolated from a Bacillus subtilis subsp. spizizenii strain cultivated from Allium cepa , also known as the common onion, which exhibited strong antibacterial activity against S. aureus ATCC 25923 [ 44 , 45 ]. The mode of action of this peptide on S. aureus was elucidated by the authors to occur through changes in the membrane potential and by triggering the production of reactive oxygen species (ROS) [ 44 , 45 ].…”
Section: Amps From Plantsmentioning
confidence: 99%